2022
DOI: 10.1101/2022.01.07.22268854
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two schizophrenia imaging signatures and their associations with cognition, psychopathology, and genetics in the general population

Abstract: The prevalence and significance of schizophrenia-related phenotypes at the population-level are debated in the literature. Here we assess whether two recently reported neuroanatomical signatures of schizophrenia, signature 1 with widespread reduction of gray matter volume, and signature 2 with increased striatal volume, could be replicated in an independent schizophrenia sample, and investigate whether expression of these signatures can be detected at the population-level and how they relate to cognition, psyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The optimal number of clusters was determined when ARI was the largest. As done in previous studies (Chand et al, 2020(Chand et al, , 2022Varol et al, 2017), we identified optimal subtypes of OCD from 1 to 6 using 10-fold cross validation where age, sex, and education level were included as covariates. The workflow is shown in Figure 1.…”
Section: Subtyping With Hydramentioning
confidence: 99%
“…The optimal number of clusters was determined when ARI was the largest. As done in previous studies (Chand et al, 2020(Chand et al, , 2022Varol et al, 2017), we identified optimal subtypes of OCD from 1 to 6 using 10-fold cross validation where age, sex, and education level were included as covariates. The workflow is shown in Figure 1.…”
Section: Subtyping With Hydramentioning
confidence: 99%
“…One challenge to the appropriate quantification of PET images is the partial volume effect [35] which was accounted for in our study by using a state-of-the-art parallel level set (PLS) regularization-based partial volume correction method [36]. To harmonize multi-scanner datasets, we relied on our previously used and validated approach [27,32] in which we used data from all study participants to compute the coefficients accounting for the effect of factors such as site, age and sex and apply them to each individual participant [37]. After correcting for the site, age, and sex covariates, we produced the harmonized DVR and used that in our analyses.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…In comparison to other schizophrenics, those with more negative symptoms exhibit more widespread cortical volume decreases [16][17][18]. However, other neuroanatomical studies have identified subtypes based on brain structure differences not otherwise detectible by clinical phenotyping [3,4,19]. The biologic etiology of schizophrenia remains unclear, and the clinical heterogeneity associated with this disorder may have frustrated attempts to gain insights into the pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have provided evidence that schizophrenia may be etiologically heterogeneous and can be divided into at least two classes with different pathophysiological signatures via behavioral and cognitive symptoms [ 1 , 2 ], cortical structure [ 3 , 4 ], gene expression patterns [ 5 , 6 , 7 , 8 ], and serum inflammation markers [ 9 , 10 , 11 , 12 ]. Despite this, most studies continue to evaluate schizophrenics as a pooled group [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation